PEMBELAJARAN KIMIA TEMATIK PADA MATA KULIAH KIMIA DASAR SEBAGAI MODEL PEMBELAJARAN BERBASIS MASALAH - Rr. Lis Permanasari & Sukisman Purtadi (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Thematic Chemistry Learning in the General Chemistry Course as aProblem-Based Learning Model. This study aims to investigate how thematicchemistry learning can be implemented and how the learning quality can beimproved through thematic chemistry learning. This study was a quasiexperimentalstudy. The participants were 49 students in the Chemistry EducationDepartment attending the General Chemistry course. The focus was on thechemistry learning quality in terms of complex learning and information processingskill and students motivation and appreciation. The data were collected throughobservations and questionnaires. The results showed that the mean for complexlearning and information process skills was 2.49 or in the good category. The meanof students motivation improved from 75.6 to 78.3 and the result of t-test was t =9.39 (p = 0.000). Students appreciation varied; some showed positive appreciationand some showed negative appreciation.Keywords: thematic chemistry learning, problem based learning, learning quality